The Research Assistant Management System (RAMS) - Amiruddin, Nurul Izzati; Sa'dan, Siti Aisyah; Mohamed, Hasiah; Mohd Adzmi, Nurul Husna Amalina (International Journal of Advanced Science Computing and Engineering, 2019)
Â The Research Management Unit (RMU) of UiTM Terengganu currentlyoperated manually in recording all of their Research Assistantinformation. The limitations in keeping the record manually are that therecord may be lost due to human or environment disaster and thestorage to keep all the record also may expended as the record are keepincreasing. The Research Assistant Management System (RAMS) isdeveloped to help the administrative of the RMU in UiTM Terengganuto manage the Research Assistant information more effectively. Reportscan be generate easily using this system. The Rapid ApplicationDevelopment (RAD) model methodology is used in the development ofthe system. The methodology consist of five phases which arerequirement planning phase, user design phase, construction phase,cutover phase and lastly the documentation. This system have beendemonstrated to three expert users for the feedback and therecommendation. Besides that, user testing also conducted bydistributed the questionnaire to the 30 respondents. The result based onthe respondent analysis shows that the highest mean of perceive ofusefulness of the system is 4.167 (SD= 0.531). In conclusions, theRAMS will give more benefit to user when using it and hopefully it canhelp RMU to manage their Research Assistant information.